The Relationship Between Age and Level of Knowledge About Menstruation and Readiness for Menarche in Grade IV - VI Female Students at Kertajaya Elementary School - Afiliany, Amelia; Ahmad Suryawan; Rize Budi Amalia (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: Menarche, the first menstruation, often elicits mixed reactions. Its occurrence is influenced by age and knowledge. Age shapes cognitive development and thinking patterns, while knowledge about menstruation affects perception. Limited knowledge and a decreasing age of menarche can hinder readiness for this milestone. Objectives: The purpose of this study is to determine the relationship between age and the level of knowledge about menstruation with readiness for menarche among fourth to sixth-grade students at SDN Kertajaya, Surabaya. Methods: This observational analytic study uses a cross-sectional design with 63 fourth to sixth-grade pre-menarche students from SDN Kertajaya, Surabaya, selected via total sampling. Data were analyzed using Spearman's rho. Results: The study revealed a significant relationship between age and readiness for menarche (p = 0.003). The proportion of girls ready for menarche increased with age: 62.5% (9–<10 years), 73.1% (10–<11 years), and 100% (11–<12 years). The negative correlation (r = -0.364) indicated that readiness for menarche improved with increasing age. Knowledge level also significantly influenced readiness for menarche (p < 0.01). Most girls with good knowledge were ready (94.3%), while no readiness was observed among those with fair or poor knowledge. The strong positive correlation (r = 0.850) showed that better knowledge was associated with higher readiness for menarche. Conclusions: There is a relationship between age and readiness for menarche, and between the level of knowledge about menstruation and readiness for menarche among fourth to sixth-grade students at SDN Kertajaya.